2016
DOI: 10.1186/s12978-016-0221-1
|View full text |Cite
|
Sign up to set email alerts
|

Out of pocket expenditure to deliver at public health facilities in India: a cross sectional analysis

Abstract: BackgroundTo expand access to safe deliveries, some developing countries have initiated demand-side financing schemes promoting institutional delivery. In the context of conditional cash incentive scheme and free maternity care in public health facilities in India, studies have highlighted high out of pocket expenditure (OOPE) of Indian families for delivery and maternity care. In this context the study assesses the components of OOPE that women incurred while accessing maternity care in public health faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
(23 reference statements)
2
34
0
Order By: Relevance
“…Medicine contributed the major portion of overall OOPE and higher overall OOPE for care seeking was associated with a priority illness which is consistent to findings in this study. A study conducted in India on OOPE to deliver public health facilities showed that an overall median OOPE was USD 11.48 (Issac et al 2016). Similar to this study, a significant predictor for high OOPE was caste.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicine contributed the major portion of overall OOPE and higher overall OOPE for care seeking was associated with a priority illness which is consistent to findings in this study. A study conducted in India on OOPE to deliver public health facilities showed that an overall median OOPE was USD 11.48 (Issac et al 2016). Similar to this study, a significant predictor for high OOPE was caste.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, each year 19 million neonates have life-threatening conditions including intrapartum related brain injury, pathological jaundice, severe bacterial infections and preterm birth which require specialized care (Bhutani et al 2013;Blencowe et al 2013;Lawn et al 2013;Lee et al 2013;Seale et al 2013). Of these, 2.9 million neonates die due to complications from preterm birth (34%), intrapartum-related conditions (25%), and infections (22%) (Lawn et al 2014). Almost all of these deaths take place in LMICs and most of them occur in families who are poor and have least access to services (Lawn et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted that the out of pocket expenditure for institutional delivery is higher than the monetary incentive provided by the government in many settings [6769]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the out‐of‐pocket fees paid by mothers in lower income and middle‐income countries . Very few studies have looked at out‐of‐pocket fees in higher income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the out-of-pocket fees paid by mothers in lower income and middle-income countries. 23,24 Very few studies have looked at out-of-pocket fees in higher income countries. One previous study from Australia has estimated costs associated with maternity care practitioners and treatments during pregnancy in 2009.…”
Section: T a B L E 3 Services Covered Undermentioning
confidence: 99%